User fees removal and community-based management of undernutrition in Burkina Faso: what effects on children’s nutritional status? - Zombré, David; De Allegri, Manuela; Ridde, Valéry; Zinszer, Kate (Public health nutrition, 2021)
Objective: - To examine the effect of an intervention combining user fees removal with community-based management of undernutrition on the nutrition status in children under 5 years of age in Burkina Faso. - - - Design: - The study was a non-equivalent control group post-test-only design based on household survey data collected 4 years after the intervention onset in the intervention and comparison districts. Additionally, we used propensity score weighting to achieve balance on covariates between the two districts, followed by logistic multilevel modelling. - - - Setting: - Two health districts in the Sahel region. - - - Participants: - Totally, 1116 children under 5 years of age residing in 41 intervention communities and 1305 from 51 control communities. - - - Results: - When comparing children living in the intervention district to children living in a non-intervention district, we determined no differences in terms of stunting (OR = 1·13; 95 % CI 0·83, 1·54) and wasting (OR = 1·21; 95 % CI 0·90, 1·64), nor in severely wasted (OR = 1·27; 95 % CI 0·79, 2·04) and severely stunted (OR = 0·99; 95 % CI 0·76, 1·26). However, we determined that 3 % of the variance of wasting (95 % CI 1·25, 10·42) and 9·4 % of the variance of stunting (95 % CI 6·45, 13·38) were due to systematic differences between communities of residence. The presence of the intervention in the communities explained 2 % of the community-level variance of stunting and 3 % of the community-level variance of wasting. - - - Conclusions: - With the scaling-up of the national free health policy in Africa, we stress the need for rigorous evaluations and the means to measure expected changes in order to better inform health interventions.